Comparing Between the Amino Acid Composition of Flax Seeds Before and After Germination - Kraievska, Svitlana; Stetsenko, Natalia; Oksana, Korol (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2017)
Flax (Linum usitatissimum L.) is well known for its health benefits and chemical composition. Flax seeds are emerging as one of the key sources of phytochemicals in the functional food production. In addition, to being one of the richest sources of α-linolenic acid oil and lignans, flax seed is an essential source of high-quality protein and soluble fibre. This study aimed to evaluate the amino acids changes caused by germination. Amino acids are an important component of food. They serve as “building blocks” that make up proteins. Protein deficiency in the body leads to disruption of its normal operation – loss of memory and mental relaxation opportunities and reduce the body‘s resistance. The effectiveness of the use of protein by the body is determined by two parameters: its balance on the content of essential amino acids and the digestible (dietary) indispensable amino acid score. DIAAS has been adopted internationally as the most suitable method for routine evaluation of protein quality of foods by the Food and Agriculture Organization/World Health Organization. (FAO Food and Nutrition 92, 2013.) We used DIAAS for protein quality evaluation in flax seed and germination flaxseed.